Peningkatan Hasil Belajar Fikih Materi Zakat Fitrah Dengan Metode Discovery Learning Kelas V MI At-Taqwa - Masruri (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
In the framework of our efforts to realize good learning outcomes, and make students (learners) eager to learn, there needs to be an educator (teacher) who is professional including having their methods or strategies in teaching. A teacher is required to be able to develop an optimal learning program so that an effective and efficient learning process is realized. Research methods using action research or action research is a research model that is at the same time practising and theorizing, or combining theory while implementing in practice. The formulation in this study is How the application of the Discovery Learning Model can improve the learning outcomes of Zakat Fitrah material fiqh in class V MI At-Taqwa Tanjungrejo Kebonsari Madiun. The result of this study is concluded that the use of the discovery learning model can improve student learning outcomes, especially Fiqh subjects. This is evident in pre-learning, Cycle I to Cycle III as well as the percentage of learning completion that increases from cycleS I to III. That is with an average of 75, 79. 81 while the percentage is 72%, 94% and 100%.